2019
DOI: 10.1111/jcmm.14405
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐638 inhibits human aortic valve interstitial cell calcification by targeting Sp7

Abstract: Calcific aortic valve disease (CAVD) is a complex heart valve disease involving a wide range of pathological changes. Emerging evidence indicates that osteogenic differentiation of human aortic valve interstitial cells (hAVICs) plays a key role in valve calcification. In this study, we aimed to investigate the function of miR‐638 in hAVICs osteogenesis. Both miRNA microarray assay and qRT‐PCR results demonstrating miR‐638 was obviously up‐regulated in calcific aortic valves compared with non‐calcific valves. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It has been proved that miR-27a and miR-96 etc. regulate osteogenesis by targeting Osx (As shown in Figure 4 ) ( Zhang et al, 2011 ; Shi et al, 2013 ; Zhang et al, 2018 ; Jiao et al, 2019 ). They suppress osteogenic differentiation by decreasing Osx expression directly.…”
Section: Mirnas and Lncrnas Regulate Osx Expressionmentioning
confidence: 99%
“…It has been proved that miR-27a and miR-96 etc. regulate osteogenesis by targeting Osx (As shown in Figure 4 ) ( Zhang et al, 2011 ; Shi et al, 2013 ; Zhang et al, 2018 ; Jiao et al, 2019 ). They suppress osteogenic differentiation by decreasing Osx expression directly.…”
Section: Mirnas and Lncrnas Regulate Osx Expressionmentioning
confidence: 99%
“…Osteogenic reprogramming of AVICs has been reported to be closely related to the pathological process of CAVD ( Jiao et al, 2019 ). Abnormal M1 polarization of macrophages partially explained osteogenic calcification of AVICs in CAVD ( Lu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al showed miR-638 distinguished heart failure with reduced vs. preserved left ventricular ejection fraction and offers better diagnosis than N-terminal pro-brain natriuretic peptide [ 119 ]. Jiao et al indicated that miR-638 is upregulated in human calcific aortic valves (hAVICs) compared with non-calcific valves and was significantly upregulated during hAVICs osteogenic differentiation [ 120 ]. This constitutes a promising noninvasive diagnostic as well as prognostic biomarker in cardiovascular pathologies risk.…”
Section: Role Of Mir-638 In Cadmentioning
confidence: 99%